Jak měřit metakognici (nejen) u nadaných dětí - Straka, Ondřej (Masaryk University Press, 2021)
Title in English: How to measure metacognition (not just) in gifted children. The publication deals with the topic of measuring metacognition, with special emphasis on a specific group of intellectually gifted children. It briefly presents the construct of metacognition itself, its relation to intellectual giftedness, together with a taxonomy of metacognitive phenomena. Next, the most important methods developed to assess metacognition are discussed and critically appraised. The monography covers both the methods, in which the data are registered during the execution of the stimulus task (on-line methods), and the methods, where the data are recorded with some time lag (off-line methods). The most extensive part of the publication is devoted to the topic of various measures, used to express the level of metacognitive monitoring.